2015
DOI: 10.1007/s11262-015-1208-7
|View full text |Cite
|
Sign up to set email alerts
|

Phage display for identifying peptides that bind the spike protein of transmissible gastroenteritis virus and possess diagnostic potential

Abstract: The spike (S) protein of porcine transmissible gastroenteritis virus (TGEV) is located within the viral envelope and is the only structural protein that possesses epitopes capable of inducing virus-neutralizing antibodies. Among the four N-terminal antigenic sites A, B, C, and D, site A and to a lesser extent site D (S-AD) induce key neutralizing antibodies. Recently, we expressed S-AD (rS-AD) in recombinant form. In the current study, we used the rS-AD as an immobilized target to identify peptides from a phag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…The S protein of TGEV near the N terminal portion (S1) has four antigenic epitopes [26]. Researchers have reported that the S1 gene could induce better immune responses than the full-length TGEV S gene in mice [24].…”
Section: Discussionmentioning
confidence: 99%
“…The S protein of TGEV near the N terminal portion (S1) has four antigenic epitopes [26]. Researchers have reported that the S1 gene could induce better immune responses than the full-length TGEV S gene in mice [24].…”
Section: Discussionmentioning
confidence: 99%
“…The S protein of TGEV has four antigenic epitopes near the N terminal portion (S1) [25] . The S1 gene has been reported to induce more impactful immune responses than the full-length S gene of TGEV in piglets [6] .…”
Section: Discussionmentioning
confidence: 99%
“…For the phage ELISA, an anti–M13-HRP mAb (GE Healthcare Life Science, 1:5000 v/v) was used. For other ELISAs, a goat anti-human IgG HRP (BioLegend, 1:5000 v/v) was used [22] . The data were processed using Graphpad Prism 5.…”
Section: Methodsmentioning
confidence: 99%